Pay equity: Equal value to whom? - Waluchow, Wil (Journal of business ethics, 1988)
This paper is an exploration of the concept “equal value” as it applies to pay equity. Following a brief discussion of several standard objections to pay equity legislation, the paper considers a number of different criteria which are employed in determining equal value or worth. Two in particular are isolated for extended discussion: the desert and the contribution criteria. The paper concludes with a major concern about the phrase “equal value to the employer.” This concern becomes pressing once the desert and contribution criteria are distinguished.